Phytoremediation Method Ability To Purify Indoor Air Pollution - Gita Cemara; Jasmine Wardiningsih; Stepalin Yunipahothon; Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2022)
Phytoremediation is a technique that uses green plants, such as spices (e.g., Thlaspi Caerulescens, Brassica Juncea, Helianthus annuus) and woody plants (e.g., Salix spp, Populus spp), to eliminate, absorb, or convert different hazardous chemicals to the environment, such as heavy metals.